The role of goodwill (business reputation) of the enterprise to strengthen its market position (Путеводитель предпринимателя)
An Effective instrument to strengthen the positions in competition acts strengthening the image of the companies that have goodwill. In this regard, the research components of goodwill of companies — the impact on the market, reputation technical competence, international relations, marketing methods require deeper theoretical-methodological analysis and elaboration specific to sectors.